A Picture of Health : Northern Ireland findings : a summary of findings from a survey exploring the health of people in temporary accommodation and other homelessness service settings.: Northern Ireland findings : a summary of findings from a survey exploring the health of people in temporary accommodation and other homelessness service settings. ([2018]) - Northern Ireland., Public Health Agency,; Council for the Homeless Northern Ireland,
No abstract available